Comparison of different treatment methods on macro-micro characteristics of Yellow River silt solidified by MICP technology. Issue 4 (3rd April 2023) - Wang, Yuke; Wang, Gan; Zhong, Yanhui; Shao, Jinggan; Zhao, Jiancang; Li, Dongbiao
Abstract: The cementation of Yellow River silt into green and sustainable building materials through microbial induced calcium carbonate precipitation (MICP) is a novel technology with a wide range of applications. The MICP treatment of abandoned Yellow River silt was carried out by multiple-phase injection method and pre-mixing method in this paper. The effects of cementation solution concentration and treatment times on the chemical conversion efficiency were investigated, and the effectiveness of the two treatment methods in improving the mechanical properties of Yellow River silt was evaluated. The results showed that the chemical conversion efficiency of the pre-mixing method was about 5% higher than that of the multiple-phase injection method. With the increase of the cementation solution concentration and the treatment times, the unconfined compressive strength (UCS) of the samples treated by the pre-mixing method increased faster and the distribution of calcium carbonate (CaCO3 ) was more uniform. After ten treatments, the UCS of the samples treated by pre-mixing method exceeds 5 MPa with a relatively uniform CaCO3 content of 25%.